Peningkatan Kreativitas Siswa SMK Melalui Pengenalan Dasar Digital Marketing Berbasis AI - Siregar, Dodi; Rahayu, Sri; Saputra, Imam; Sari, Dian Purnama; Sari, Vina Winda (Jurnal Pengabdian Masyarakat Inovasi, 2026)
This community service program aimed to enhance the creativity of vocational high school students through the introduction of basic artificial intelligence (AI)-based digital marketing. The implementation method included literature review, partner needs assessment, and hands-on training involving 20 participants. The results revealed a significant improvement in participants’ understanding, where initially 80% were categorized as low, but after the training, 60% were categorized as good. Satisfaction responses also indicated that most participants felt satisfied or highly satisfied with the materials and delivery methods. This program demonstrates that introducing AI-based digital marketing can serve as an effective approach to foster 21st-century skills among vocational school students. However, the limitation of this activity lies in its short duration, which restricted the coverage of advanced materials, yet it provides a strong foundation for future community service initiatives.